ESTABLISHMENT AND PARTIAL CHARACTERIZATION OF FETAL FIBROBLAST CELLS OF BLACK BENGAL BREED - BORAH, BISWAJYOTI; SINGH, A P; PANDEY, S K; JAIN, T (The Indian Journal of Animal Sciences, 2022)
Animal cells are a valuable genetic resource and become the major tool for routine investigation of biological research and regenerative medicine. The somatic cells are as valuable as germ cells and an attractive resource for conserving animal genetic materials. The present study was to establish and characterized the caprine fetal fibroblast cell culture of Back Bengal goat's genetic resources; the breed is one of the highly prolific breeds among Indian breeds of goat and famous for meat and skin. The fetal fibroblast cells of Back Bengal goat breed at the age of 1-2 month was cultured. The cells were highly prolific, able to identify by molecular markers, with a population doubling time (PDT) approximately 73.6 hours and could be useful for gene expression study. These cells will be valuable assets for other genomics, post genomics, somatic cloning, and other fields of biological sciences in the future.